Benchmark Ditopic Binding of Cl− and Cs+ by the Macrocycle Hexacyclen. Issue 10 (21st March 2017) - Avilés‐Moreno, Juan Ramón; Berden, Giel; Oomens, Jos; Martínez‐Haya, Bruno
Abstract: The ditopic binding of organic and inorganic anions and cations constitutes a distinct feature of polyazamacrocycles that underlies their action as intermediate docking and exchange ionophoric sites for tailored supramolecular synthesis and sensors. This work investigates the Cl − and Cs + complexes formed by hexacyclen (1, 4, 7, 10, 13, 16‐hexaazacyclooctadecane, ha18c6), a benchmark building block of ion‐pair polyamine receptors. IR action spectroscopy is employed to characterize the anionic and cationic complexes under controlled environmental conditions in an ion trap. This allows for accurate modeling of the isolated complexes with quantum chemical computations. A comparison of the experimental and computational spectra serves to assess the low‐energy conformers dominantly populated at room temperature, which comprise, in both cases, three structures of Cs, C 2, and C 3 v symmetry with relative energies within about 5 kJ mol −1 . The ion‐pair complex Cl − –ha18c6–Cs + is predicted to host the cation and anion on opposite sides of the macrocycle in a C 3 v conformation that does not correlate with the lowest energy structures of the binary complexes. This indicates that the formation of the ion‐pair complex in its most stable conformation demands a rearrangement of the hexacyclen ring structure upon the incorporation of the counterion. Abstract : Backbone arrangements : The Cl − and Cs + complexes formed by 1, 4, 7, 10, 13, 16‐hexaazacyclooctadecane (hexacyclen), a benchmark building block of ion‐pair polyamine receptors, are investigated. The most stable conformers, dominantly populated at room temperature, comprise three structures of C s, C2, and C3 v symmetry. A marked rearrangement of the macrocycle backbone is predicted upon formation of the ion‐pair complex.